Diagnostik und Therapie von Frauen mit wiederholten Spontanaborten. Leitlinie der DGGG, OEGGG und SGGG (S2k-Level, AWMF-Registernummer 015/050, Mai 2022) - Toth, Bettina; Bohlmann, Michael; Hancke, Katharina; Kuon, Ruben; Nawroth, Frank; von Otte, Sören; Rogenhofer, Nina; Rudnik-Schöneborn, Sabine; Schleußner, Ekkehard; Tempfer, Clemens; Vomstein, Kilian; Wischmann, Tewes; von Wolff, Michael; Würfel, Wolfgang; Zschocke, Johannes (Geburtshilfe und Frauenheilkunde, 2022)
Purpose The aim of this guideline is to standardize the diagnosis and therapy of recurrent miscarriage (RM) using evidence from the recent literature. This is done by using consistent definitions, objective evaluations and standardized treatment protocols.Methods When this guideline was compiled, special consideration was given to previous recommendations in prior versions of this guideline and the recommendations of the European Society of Human Reproduction and Embryology, the Royal College of Obstetricians and Gynecologists, the American College of Obstetricians and Gynecologists and the American Society for Reproductive Medicine, and a detailed individual search of the literature about the different topics was carried out.Recommendations Recommendations about the diagnostic and therapeutic procedures offered to couples with RM were developed based on the international literature. Special attention was paid to known risk factors such as chromosomal, anatomical, endocrinological, physiological coagulation, psychological, infectious and immune disorders. Recommendations were also developed for those cases where investigations are unable to find any abnormality (idiopathic RM).Ziel Ziel der vorliegenden Leitlinie ist es, die Diagnostik und Therapie von wiederholten Spontanaborten (WSA) anhand der aktuellen Literatur evidenzbasiert zu standardisieren. Dies erfolgt unter Verwendung einheitlicher Definitionen, objektivierter Bewertungsmöglichkeiten und standardisierter Therapieprotokolle.Methoden Die Erstellung dieser Leitlinie erfolgte unter besonderer Berücksichtigung der bisherigen Empfehlungen der Vorversionen dieser Leitlinie, den Empfehlungen der European Society of Human Reproduction and Embryology, des Royal College of Obstetricians and Gynecologists, des American College of Obstetricians and Gynecologists und der American Society for Reproductive Medicine sowie einer ausführlichen individuellen Literaturrecherche zu den jeweiligen Themen.Empfehlungen Es wurden Empfehlungen zur Diagnostik und Therapie von Paaren mit WSA anhand der internationalen Literatur erarbeitet. Insbesondere wurde auf die bekannten Risikofaktoren wie chromosomale, anatomische, endokrinologische, gerinnungsphysiologische, psychologische, infektiologische und immunologische Störungen eingegangen. Aber auch für die Fälle einer unauffälligen Abklärung (idiopathische WSA) wurden Empfehlungen erarbeitet.
Keywords: guideline; recurrent miscarriage; recurrent pregnancy loss; incidence; diagnosis; therapy